Reply - Ramos, Alcida (Brasília DF: Universidade de Brasília Instituto de Ciências Sociais Departamento de Antropologia, 2023)
This is probably the first academic debate between interethnic anthropologists about the possible transformations of our discipline triggered by the arrival of indigenous practitioners. After glancing at texts written by indigenous people in other countries, I have not found anything similar, only the recurring – and perfectly understandable – issue of western colonization and its effects on indigenous peoples around the world. Native anthropologists from the United States, Canada, and elsewhere in the Americas expose their difficulties as native professionals in the academic milieu, but do not try to change the discipline. Important works, such as those by Linda Tuhiwai Smith (Maori, New Zealand), Margaret Kovach (First Nations, Canada), Shawn Wison (Cree, Canada), Gregory Cajete (Tewa, United States), and Devon Mihesuah (Choctaw, United States), among many others, focus on developing indigenous research methods. Important contributions as these are to improve knowledge in the academy, their goal is to devise scientific procedures apart from Western canons. In turn, we try to go a little farther. We bring up indigenous procedures to produce and acquire knowledge as an attempt to change certain traditional academic habits, particularly in anthropology. Muito provavelmente, este é o primeiro debate acadêmico entre antropólogos interétnicos sobre o potencial de transformação da disciplina antropológica que a chegada de profissionais indígenas enseja. Após um rápido exame de textos escritos por indígenas em diversos países, não encontrei nada semelhante, apenas o tema recorrente, e compreensível, dos efeitos da colonização ocidental sobre povos indígenas ao redor do mundo. Antropólogos indígenas nos Estados Unidos, Canadá e outros países, principalmente das Américas, expõem as dificuldades que profissionais nativos enfrentam nos meios acadêmicos, mas não encontrei tentativas de influir no devir da disciplina. Importantes iniciativas, como as de Linda Tuhiwai Smith (Maori, Nova Zelândia), Margaret Kovach (First ...